AB0245 Performance of the eular definition of arthralgia suspicious for progression to rheumatoid arthritisin combination with musculoskeletal ecography with doppler (USMD) in clinical practice. (12th June 2018) - Calvo Gutiérrez, J.; Aranda-Valera, I.C.; Sastre Dominguez, M.A.; Ortega Castro, R.; Castro Villegas, M.C.; Escudero Contreras, A.; Collantes Estevez, E.
Abstract : Background: The treatment at an early stage of rheumatoid arthritis (RA), even in the undifferentiated phase, which can prevent the progression and even the reversal of the inflammatory process 1 . Identification in the preclinical phase is complicated. The detection of joint inflammatory activity through the use of UsMD would be useful for diagnosis in arthargia suspicious for progression to RA (CSA) 2 . Objectives: To assess the usefulness of the EULAR definition of CSA in clinical practice. To Describe the clinical, serological and ultrasound characteristics and the CSA evolution over time (0, 3, 6 months). To determine the clinical and ultrasound characteristics that could influence in the RA progression. Methods: A longitudinal prospective study that includes 27 patients referred from primary care (PC) or Rheumatology consultations with CSA according to EULAR criteria of more than 8 weeks and less than 6 months of evolution. All patients were evaluated at 0–3–6 months, including at each visit: serological parameters (RF, ACPA, ESR, CRP), measures of functionality (HAQ) and activity (DAS28); and image (Xray and UsMD). The ultrasound examination included: carpus (palmar and dorsal planes), MCFs 2°−5°, extensor cubital tendons, ankles, posterior tibialis, 5° MTFs and painful IFPs in a comparative and bilateral model. The Us scans were performed by the same researcher without access to the clinical data of the patients, collected by another independent researcher. Proportions were compared using the chi-square test to see which factors were related to RA development. Results: 27 patients with CSA criteria according to EULAR definition have included. 59.3% were derived from PC, 92.6% were women with a mean age of 48.5 years (DS 11.95) and active labour 77.8%. Ten patients (37%) were smokers and dyslipidemics with an atherogenic index of 3.19 (DS1.04). 60.95% presented slight overweight with a BMI of 27.65 Kg/m2 (DS 5.7). The most frequent form of presentation was polyarticular 12 (50%) followed by oligoarticular. 57.7% of the cases had symmetric involvement and 81.5% a duration of symptoms between 6–16 weeks. 52% patients presented RF +and 4 ACPA and ANA+. During the follow-up: 8 patients (29.6%) were classified as RA (ACR/, EULAR 2010 all of them derived from Rheumatology, 3 (11.1%) microcrystalline arthritis, 1 Sjogren primary syndrome and 15 (55.5%) presented degenerative or tendinous pathology. In those patients who progressed to RA, we only found a statistical association with the presence of high RF +and with the presence of doppler at the carpal level (p=0.048). Conclusions: The results of our study suggest that the EULAR definition of CSA, although more useful when used by rheumatologists, does not reach sufficient accuracy for the diagnosis of RA, while the presence of subclinical synovitis detected by UsMD could be useful. The highest levels of RF were related to the presence of synovitis in our cohort, unlike ACPA. Further studies would be needed to recommend its introduction into clinical practice and, in our opinion should be considered in future sets of classification criteria. References: [1] Van der helm-van mil A, et al. Arthritis Rheum2007;56(2):433–40. [2] Van Steenbergen HW, et al. Ann Rheum Dis2017;76:491–6. Disclosure of Interest: None declared